PENERAPAN TEKNIK EDITING PADA VIDEO (PODCAST OSARI BINA DARMA TV) PALEMBANG - Geni Andrio; Dimas Umboro (Jurnal Cakrawala Ilmiah, 2025)
his study aims to understand how editing techniques are applied to the OSARI podcast videos of Bina Darma TV Palembang. The OSARI podcast is a flagship program broadcast by Bina Darma TV, playing an important role in delivering information to the audience. The editing techniques used in podcast videos affect the quality of visuals and the messages being conveyed. In this research, the author examines editing techniques such as cutting, transitions, visual effects, and audio arrangement to support the content. The research method used is descriptive with a qualitative approach, involving observation and interviews with the production team of Bina Darma TV. The findings show that proper editing techniques can enhance visual quality and make messages easier for the audience to understand. Accurate editing also helps ensure smooth video flow and improves audio quality for a more pleasant listening experience. In conclusion, editing techniques are crucial for the success of the OSARI podcast in reaching its audience effectivelyTop of FormBottom of Form